The Legacies of Institutionalisation Disability, Law and Policy in the 'Deinstitutionalised' Community - Spivakovsky, Claire; Steele, Linda; Weller, Penelope (Oñati International Series in Law and Society, 2020)
This is the first collection to examine the legal dynamics of deinstitutionalisation. It considers the extent to which some contemporary laws, policies and practices affecting people with disabilities are moving towards the promised end point of enhanced social and political participation in the community, while others may instead reinstate, continue or legitimate historical practices associated with this population's institutionalisation. Bringing together 20 contributors from the UK, Canada, Australia, Spain and Indonesia, the book speaks to overarching themes of segregation and inequality, interlocking forms of oppression and rights-based advancements in law, policy and practice. Ultimately this collection brings forth the possibilities, limits and contradictions in the roles of law and policy in processes of institutionalisation and deinstitutionalisation, and directs us towards a more nuanced and sustained scholarly and political engagement with these issues.